The Role of Trust and Migrant Investments in DiasporaHomeland Development Relations (African Human Mobility Review, 2021)
Research into the role of diaspora communities in origin countries’ developmentis a growing phenomenon. However, there is little understanding of the role oftrust in mediating transnational relationships between migrants and recipientsof remittances (non-migrants, members of migrant households and communityleaders). Using a case study methodology, mixed methods and a comparativeapproach – in-depth interviews with 40 key informants (20 in the UK and 20 inGhana), 120 questionnaires administered in the UK and 346 questionnairesadministered in Ghana – this paper examines differing conceptualisations oftrust among ‘development partners’ in the process of negotiating as well asimplementing migrant-funded development projects. It also examines the natureof investments of migrants in the origin country. Migrant respondents are fromthe Kwahuman Traditional Area and the Upper East Region of Ghana. Ghana isused as a case study to examine this phenomenon both from the perspective ofthe migrant and that of the origin country partners. Narratives by migrants areexamined in order to unearth factors that inform their decision-making and theapproaches they adopt to ensure accountability.